Contorted aromatics via a palladium-catalyzed cyclopentannulation strategy. Issue 18 (7th September 2015) - Bheemireddy, Sambasiva R.; Ubaldo, Pamela C.; Finke, Aaron D.; Wang, Lichang; Plunkett, Kyle N.
Abstract : A palladium-catalyzed cyclopentannulation provides access to contorted aromatics that afford solubility benefits while maintaining pi–pi stacking motifs. Abstract : We show that a new class of contorted polycyclic aromatic hydrocarbons (PAHs) containing five-membered rings can be prepared via a palladium-catalyzed cyclopentannulation followed by Scholl cyclodehydrogenation. The annulation chemistry can be accomplished between a di-arylethynylene and an appropriate aryl-dibromide to form 1, 2, 6, 7-tetraarylcyclopenta[ hi ]aceanthrylenes and 1, 2, 6, 7-tetraaryldicyclopenta[ cd, jk ]pyrenes. Scholl cyclodehydrogenation to close the externally fused aryl groups was accomplished only with properly arranged alkoxy substitutions and provides access to the pi-extended 2, 7, 13, 18-tetraalkoxytetrabenzo[ f, h, r, t ]rubicenes and 2, 7, 13, 18-tetraalkoxydibenzo[4, 5:6, 7]indeno[1, 2, 3- cd ]dibenzo[4, 5:6, 7]indeno[1, 2, 3- jk ]pyrenes. The final compounds each possess apparent [4]helicene-like arrangements with fused five-membered rings; however, only the 2, 7, 13, 18-tetraalkoxytetrabenzo[ f, h, r, t ]rubicenes contort out of planarity owing to an additional [5]helicene like arrangement. Single crystal analysis of the contorted aromatic shows the PAHs stack in a lock-and-key like arrangement and pi-stack in a columnar arrangement. Solution-phase aggregation, as well as liquid crystalline mesophases, were found for derivatives with suitably attached solubilizing chains.